Science, Technology and Innovation Policy for the Future Potentials and Limits of Foresight Studies - Meissner, Dirk.; Gokhberg, Leonid; Sokolov, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book gives practical guidance for policy makers, analysts and researchers on how to make the most of the potential of Foresight studies. Based on the concept of evidence-based policy-making, Foresight studies are common practice in many countries and are commonly understood as a supportive tool in designing future-oriented strategies. The book outlines approaches and experiences of integrating such Foresight studies in the making and implementation of science, technology and innovation (STI) policies at different national levels. It delivers insights into practical approaches of developing STI policy measures oriented towards future societal and technological challenges based on evidence drawn from comparable policy measures worldwide. Authors from leading academic institutions, international organizations and national governments provide a sound theoretical foundation and framework as well as checklists and guidelines for leveraging the potential impact of STI policies.
1 The Meaning of Foresight in Science Technology and Innovation Policy - An Introduction -- Section I: Instruments and Tools for Foresight Studies -- Section II: Foresight Instruments for Innovative Markets -- Section III: Country Foresight Studies -- Section IV: Foresight Studies - Instrument for Innovative Policy? - 16 Summary - Targeting STI Policy Interventions - Future Challenges for Foresight.
Keywords: Economics; Entrepreneurship; Economics/Management Science; R & D/Technology Policy; Innovation/Technology Management; Comparative Politics; Entrepreneurship